Formulasi sediaan lip cream ekstrak etanol bunga kecombrang (Etlingera elatior (Jack) R. M. Sm.) dan bunga rosella (Hibiscus sabdariffa L.) sebagai zat pewarna alami - Rumanti, Ruth Mayana; Sari , Rika Puspita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Introduction: The kecombrang flower and roselle flower are known as sources of natural antioxidants and have the potential to be used as natural dyes in lip cream products. Both types of flowers contain compounds such as tannins, flavonoids, and saponins. The aims of study to analyze the effect of varying concentrations of ethanol extract from the kecombrang flower (Etlingera elatior (Jack) R. M. Sm.) and the roselle flower (Hibiscus sabdariffa L.) on the color of lip cream formulations. The method of research was conducted through laboratory experiments that included sampling, extract preparation, product formulation, physical quality evaluation, and panelist preference testing. Data were analyzed descriptively by calculating the percentage of preference levels and presented in the form of tables and graphs. The results show that the preparation has a semi-solid texture, with colors ranging from light pink to dark pink in certain combinations, and a purplish pink for the 10% roselle extract formulation. The pH of the preparation is in the range of 5.1-5.4, without coarse grains, good spreadability, an average spread distance of 5.5 cm, an average adhesion time of 12.73 seconds, and no irritation. The cycling test indicates color instability, changing from light pink to dark brownish purple. Based on the hedonic test, formulation F5 has the highest preference level, which is 88.33%. The conclusion of this study is that the ethanol extract of kecombrang and rosella flowers produces a light pink lip cream that is suitable for formulation in lip cream preparations. The higher the concentration of the extract used, the darker the pink color produced, with a texture that tends to be more liquid and a decreasing pH.